THE RHETORIC OF BARTÓK’S MELODIC WORLD - István ANGI (Studia Universitatis Babeş-Bolyai. Musica, 2009)
As looking through an encyclopaedia, one come across the presentation of the Baroque and the way it influenced the work of Bartók as well the succinct presentation of the melodic world of the same composer. The next step would be to go to the practical examples of the same Bartók and to use as a first example, the world of metaphors that abounds in his work. After the theory, one come across the practical example in the form of the well-chosen examples, which are inserted in the text as if they are closely connected to the word that precedes them. As an example, we can remind of the “sigh” that follows everyone who hears it by his or her own will or by mistake and which is illustrated in an example that is very easy to remember. However, these are only a few lines, but these lines give a taste of the world of music of one wonderful composer.